A Look at Canada's Provincial and Territorial Geological Surveys - Boon, Jan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1998)
Summary This paper gives an overview of Canada's provincial and territorial geological surveys as of late 1998. It describes the history and current activities of each briefly. A summary table provides information on the size of each organization, expertise, budget, locations and contacts.